2005
DOI: 10.1074/jbc.m413411200
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Endothelial Aggregation Receptor 1 (PEAR1), a Novel Epidermal Growth Factor Repeat-containing Transmembrane Receptor, Participates in Platelet Contact-induced Activation

Abstract: The present study was designed to identify novel membrane proteins that signal during platelet aggregation. Because one putative mechanism for signaling by a membrane protein involves phosphorylation, we used oligonucleotide-based microarray analyses and mass spectrometric proteomics techniques to specifically discover membrane proteins and also identify those proteins that become phosphorylated on tyrosine, threonine, or serine residues upon platelet aggregation. Surprisingly, both techniques converged to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
135
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 27 publications
4
135
0
Order By: Relevance
“…Interestingly however, it was postulated by Herrera-Galeano et al 44 that increased expression of PEAR1 might be an important cause of hyperactivity. Here, we have demonstrated that genetic variation within PEAR1, particularly rs41299597, which codes for the S802C amino acid substitution in a potential phosphorylation site in the cytoplasmic domain, 43 is associated with an increased expression of PEAR1 in activated platelets as well as increased responsiveness through the GPVI receptor. That 2 of the 4 SNPs in PEAR1 were identified as a result of exon sequencing highlights the importance of the identification of rare SNPs in genotype-phenotype studies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly however, it was postulated by Herrera-Galeano et al 44 that increased expression of PEAR1 might be an important cause of hyperactivity. Here, we have demonstrated that genetic variation within PEAR1, particularly rs41299597, which codes for the S802C amino acid substitution in a potential phosphorylation site in the cytoplasmic domain, 43 is associated with an increased expression of PEAR1 in activated platelets as well as increased responsiveness through the GPVI receptor. That 2 of the 4 SNPs in PEAR1 were identified as a result of exon sequencing highlights the importance of the identification of rare SNPs in genotype-phenotype studies.…”
Section: Discussionmentioning
confidence: 91%
“…The PEAR1 gene has only recently been described in platelets and endothelial cells. 43 Herrera-Galeano et al recently reported an association between rs2768759, a SNP 10 kb upstream of PEAR1 that maps to the NTRK1 gene, and platelet aggregation in response to collagen and epinephrine in a white American cohort and to ADP and epinephrine in a black American cohort. 44 Neither this SNP, nor SNPs that are in LD, were included in the genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Expression was quantified via the DDCt method 14 and expressed in arbitrary units (defined in figure legends) or in percentage compared with control. Expression of genes included in the PI3K/Akt (reference PAHS-058A) and Notch (reference PAHS-059A) RT 2 Profiler signaling was analyzed by qRT-PCR (SABioscience, Qiagen). Cell populations transduced by control lentivirus were used as a reference for LV_miR_PEAR1-transduced cells.…”
Section: Pcr and Real-time Qrt-pcrmentioning
confidence: 99%
“…1,2 We recently reported that interactions between PEAR1, Src family kinases (C-src and Fyn), and the p85/phosphatidylinositol 3-kinase 3-kinase (PI3K) subunit constitute a signaling complex, causing sustained aIIbb3 activation via Akt phosphorylation. 1 In addition to its role in platelet function, a potential role for PEAR1 in hematopoietic cell regulation has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…1 In platelets, PEAR1 is involved in cell activation through its engagement in sustaining activation of the platelet integrin, a IIb b 3 , 2 and platelet FceR1a has been identified as one of its activating ligands.…”
Section: Introductionmentioning
confidence: 99%